Symbiotic vs. asymbiotic seed germination in epiphytic orchids (2009)
We compared seedling growth of the epiphytic orchid, Tolumnia variegata in agar media with and without inoculated mycorrhizal fungi. Symbiotic germination produced more-developed embryos than asymbiotic germination. Differences were highly significant, although some isolates of Rhizoctonia-like fungi were parasitic on seeds. Control seeds in a cellulose medium without Rhizoctonia-like fungi did not germinate. Seeds of Epidendrum ramosum, Lepanthes rupestris and Psychilis monensis showed no significant differences between asymbiotic and symbiotic germination using mycorrhizal fungi isolated from T. variegata roots, suggesting high mycorrhizal specificity. Our data suggest that the relationship between epiphytic orchids and the mycorrhizal fungi is more specific than previously thought. The use of the right fungal strain may enhance germination performance. Orchid growers may achieve better results in the propagation of some epiphytic orchids using symbiotic germination.